2017
DOI: 10.1002/wps.20438
|View full text |Cite
|
Sign up to set email alerts
|

The contemporary refugee crisis: an overview of mental health challenges

Abstract: There has been an unprecedented upsurge in the number of refugees worldwide, the majority being located in low-income countries with limited resources in mental health care. This paper considers contemporary issues in the refugee mental health field, including developments in research, conceptual models, social and psychological interventions, and policy. Prevalence data yielded by cross-sectional epidemiological studies do not allow a clear distinction to be made between situational forms of distress and fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
432
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 541 publications
(473 citation statements)
references
References 91 publications
10
432
0
5
Order By: Relevance
“…Syrian refugees may have been exposed to multiple war-related stressors such as torture, rape, witnessing the death of family members as well as the destruction of their homes and livelihoods, and they have undertaken a risky and stressful flight leaving their homeland for an unknown future (Silove, Ventevogel, & Rees, 2017). In addition to experiences of major loss and potentially traumatic experiences in their country of origin, Syrian refugees are also affected by stressful circumstances in host countries, where the capacity for self-help and mutual support has been negatively impacted by forced migration, the separation from families and communities, collective violence and mistrust.…”
Section: Introductionmentioning
confidence: 99%
“…Syrian refugees may have been exposed to multiple war-related stressors such as torture, rape, witnessing the death of family members as well as the destruction of their homes and livelihoods, and they have undertaken a risky and stressful flight leaving their homeland for an unknown future (Silove, Ventevogel, & Rees, 2017). In addition to experiences of major loss and potentially traumatic experiences in their country of origin, Syrian refugees are also affected by stressful circumstances in host countries, where the capacity for self-help and mutual support has been negatively impacted by forced migration, the separation from families and communities, collective violence and mistrust.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data from refugees experiencing torture showed that while 19% had PTSD, 32% fulfilled CPTSD criteria 4 . It is important to estimate both PTSD and CPTSD, as these conditions may correlate with different variables and require distinct interventions 7,8 .…”
mentioning
confidence: 99%
“…Befriending schemes and community based health awareness programmes provide support, combat isolation, assist with navigation of health services, and help to link migrant and local communities 52122…”
Section: What Health Problems Do Forced Migrants Face?mentioning
confidence: 99%